HIV infection and placental malaria reduce maternal transfer of multiple antimalarial antibodies in Mozambican women. Issue 4 (April 2021) - Alonso, Selena; Vidal, Marta; Ruiz-Olalla, Gemma; González, Raquel; Jairoce, Chenjerai; Manaca, M. Nelia; Vázquez-Santiago, Miquel; Balcells, Reyes; Vala, Anifa; Rupérez, María; Cisteró, Pau; Fuente-Soro, Laura; et al.
Highlights: Maternal antibody levels are the main determinant of cord antibody levels. HIV infection reduced cord antimalarial IgG and IgG1 levels and placental transfer. Placental malaria reduced cord levels and transfer of antimalarial IgG. Summary: Objectives: Maternal Plasmodium falciparum -specific antibodies may contribute to protect infants against severe malaria. Our main objective was to evaluate the impact of maternal HIV infection and placental malaria on the cord blood levels and efficiency of placental transfer of IgG and IgG subclasses. Methods: In a cohort of 341 delivering HIV-negative and HIV-positive mothers from southern Mozambique, we measured total IgG and IgG subclasses in maternal and cord blood pairs by quantitative suspension array technology against eight P. falciparum antigens: Duffy-binding like domains 3-4 of VAR2CSA from the erythrocyte membrane protein 1, erythrocyte-binding antigen 140, exported protein 1 (EXP1), merozoite surface proteins 1, 2 and 5, and reticulocyte-binding-homologue-4.2 (Rh4.2). We performed univariable and multivariable regression models to assess the association of maternal HIV infection, placental malaria, maternal variables and pregnancy outcomes on cord antibody levels and antibody transplacental transfer. Results: Maternal antibody levels were the main determinants of cord antibody levels. HIV infection and placental malaria reduced the transfer and cord levels of IgG and IgG1, and this was antigen-dependent. Low birth weight was associated with an increase of IgG2 in cord against EXP1 and Rh4.2. Conclusions: We found lower maternally transferred antibodies in HIV-exposed infants and those born from mothers with placental malaria, which may underlie increased susceptibility to malaria in these children.